Impacts of Climate Change on the Distribution of the Red-Shanked Douc (Pygathrix nemaeus) - Tuan Anh, Nguyen; Tien Phong, Nguyen; Thi Dieu Quynh, Tran; Thi Thu Ha, Nguyen; Vinh Thanh, Nguyen; Viet Hung, Pham; Duc Minh, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 3DO - 10.25073/2588-1094/vnuees.4975, 2023)
The Red-shanked Douc (Pygathrix nemaeus) is an endangered primate found only in a small region of Indochina, and its populations is believed to have declined at most known sites in recent decades. While the most serious threats to the Doucs to date are illegal hunting and habitat destruction, the potential impacts of climate change on this species are still poorly understood. In this study, we employ MaxEnt, a widely used species distribution modeling method, to predict climatically suitable habitat for P. nemaeus at present, and then project the optimal model using a range of future climate change scenarios to understand the possible shifts in response to climate change over the entire range of the Red-shanked Douc. The model results in most climate change scenarios and timeframes show that P. nemaeus may experience significant habitat loss and fragmentation within its current range as a consequence of suitable habitat contraction. The climatically stable refugia for the Red-shanked Douc are predicted to consist of protected areas along the Annamite Range that runs between Vietnam and Laos, and we suggest this region to be the focus of the Doucs’ conservation effort in the future. To mitigate climate-related risks for the Red-shanked Douc, future cooperation initiatives between Vietnam and Laos’ governmental institutions and conservation organizations will be crucial in conserving the remaining habitat of this endangered primate.